Detecting and targetting oncogenic fusion proteins in the genomic era. (7th April 2015) - Davare, Monika A.; Tognon, Cristina E.
Review Targetting fusion proteins in the genomic era: Our increasing knowledge of fusion proteins underscores how these unique drivers break though tissue boundaries and provides a context for common therapeutic strategies for multiple types of cancer. These studies will shape the future of cancer care and lead us into an era of precision medicine that targets specific fusions to improve patient prognosis and long‐term outcomes.